Carrageenan-induced acute inflammation in the mouse air pouch synovial model. Role of tumour necrosis factor - M. Romano; R. Faggioni; M. Sironi; S. Sacco; B. Echtenacher; E. Di Santo; M. Salmona; P. Ghezzi (Mediators of Inflammation)
We used the mouse air pouch model of inflammation to study the interaction between cytokines, prostaglandin E2 (PGE2) and cell migration during the various phases of acute local inflammation induced by carrageenan. In serum, the levels of interleukin 1 (IL-1), interleukin 6 (IL-6), tumour necrosis factor (TNF), serum amiloid-A (SAA) and Fe++ were never different from controls, indicating that no systemic inflammatory changes were induced. Locally the exudate volume and the number of leukocytes recruited into the pouch increased progressively until 7 days after carrageenan. The same was true for PGE2 production. We could not measure IL-1 but the production of IL-6 and TNF reached a maximum after 5-24 h then quickly decreased. Anti-TNF antibodies inhibited cell migration by 50% 24 h after treatment. Pretreatment with interleukin 10 (IL-10) inhibited TNF production almost completely and cell migration by 60%. Carrageenan-induced inflammation was modulated by anti-inflammatory drugs. Pretreatment with dexamethasone (DEX) or indomethacin (INDO) inhibited cell migration and reduced the concentration of TNF in the exudate. Production of PGE2 or vascular permeability did not correlate with the number of cells in the pouch. Local TNF seems to play an important role in this model, particularly for leukocyte migration in the first phase of the inflammatory process. In conclusion, the air pouch seems to be a good model for studying the regulation of the early events of local inflammation, particularly the role of cytokines and cell migration.